Update on Direct Oral Anticoagulants in Atrial Fibrillation Patients Undergoing Cardiac Interventional Procedures: From Clinical Trials to Real-World Evidence. Issue 3 (March 2020) - Melillo, Enrico; Carbone, Andreina; Rago, Anna; Papa, Andrea A.; D'. Onofrio, Antonio; Nigro, Gerardo; Golino, Paolo; Russo, Vincenzo
Abstract : Abstract: Direct oral anticoagulants (DOACs) are considered a first-line therapy for long-term stroke prevention in patients with nonvalvular atrial fibrillation (AF) and high thromboembolic risk. The potential role of DOACs in cardiac interventional procedures is a pressing clinical question, considering the increasing number of procedures and the growing prevalence of patients in DOAC therapy. The aim of this review is to provide an update on available evidence about the clinical performance of DOACs in AF patients undergoing different interventional procedures (AF cardioversion and ablation, and percutaneous coronary and structural heart disease interventions) and to explore the possible role of DOACs as an alternative therapeutic strategy in cardiac interventional procedures among non-AF patients.